2008
DOI: 10.1094/pdis-92-3-0469
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Molecular Characterization of Leaf Rust Resistance Gene Lr14a in Durum Wheat

Abstract: Leaf rust, caused by Puccinia triticina, is an important disease of durum wheat (Triticum turgidum subsp. durum) and only a few designated resistance genes are known to occur in this crop. A dominant leaf rust resistance gene in the Chilean durum cv. Llareta INIA was mapped to chromosome arm 7BL through bulked segregant analysis using the amplified fragment length polymorphism (AFLP) technique, and by mapping three polymorphic markers in the common wheat (T. aestivum) International Triticeae Mapping Initiative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 39 publications
0
30
0
5
Order By: Relevance
“…SSR markers Xgwm344 and Xgwm146 were used to detect the presence of the Lr14a gene. These markers are dominant and linked in coupling with that gene (Herrera-Foessel et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SSR markers Xgwm344 and Xgwm146 were used to detect the presence of the Lr14a gene. These markers are dominant and linked in coupling with that gene (Herrera-Foessel et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…This information is important to guide breeders in their breeding programmes and gene deployment strategies. For more than three decades, the leaf rust resistance gene Lr14a has been effective in protecting durum wheat against leaf rust in Spain The presence of this commonly occurring gene in durum wheat germplasm was first reported by Herrera-Foessel et al (2008), who also found two closely linked SSR (Single Se-2 var 'Altar C84', released in Spain as 'Gallareta'. This gene effectively protected the majority of durum wheat cultivars against the Mexican leaf rust races for nearly two decades, but the resistance it provided was overcome by the race BBG/BN in 2001 in Mexico, and later in other parts of the world (Singh et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…'Thatcher' and also significant differences between years were observed (indicated by asterisks in Table 5). Lr13 remained at a lower infection level in relation to 'Thatcher' from 2002(p<0.041) except in 2005, 2008 NILs that carry Lr13 turned out to be as susceptible as 'Thatcher ' (2007 and 2008, p=0.694; 2009 p=1.000). In these years also, changes in the infection level of Lr14 and Lr37 were observed.…”
Section: Leaf Rust Monitoring Inf Field Trialsmentioning
confidence: 95%
“…A characteristic feature of durum wheat leaf rust races is virulence to most durum wheat lines and avirulence to most Lr genes present in common wheat lines [77,78]. Thus, the resistance genes that are effective in durum wheat germplasms could be widely ineffective in common wheat lines [79]. In addition, the seedling resistance genes Lr23, Lr10, and Lr33 are not considered effective due to frequent virulence among P. triticina races [78].…”
Section: Genetic Characterization Of Leaf Rust Resistance Genesmentioning
confidence: 99%